Different Pathways of Skin Aging: Objective Instrumental Evaluation - Noah Musolff; Carmen Cantisani; Stefania Guida; Simone Michelini; Madeline Tchack; Babar Rao; Giovanni Pellacani (Diagnostics)
Background/Objectives: Hypertrophic and atrophic skin aging represent two distinct phenotypes: hypertrophic aging is marked by deep wrinkles and a leathery texture, whereas atrophic aging is characterized by overall skin thinning, increased vascularity, and a higher risk of non-melanoma skin cancers. This study aims to elucidate the characteristics and differences between hypertrophic and atrophic facial aging subtypes using two non-invasive imaging devices: VISIA® and dynamic optical coherence tomography (D-OCT). Methods: We retrospectively evaluated patients who had presented to the outpatient dermatological clinic at Policlinico Umberto I hospital in Rome, Italy for a non-invasive facial imaging check-up. We included 40 patients aged 60–75 who were imaged with VISIA® and dynamic optical coherence tomography (D-OCT). Based on the number of UV spots and amount of red found on VISIA®, subjects were grouped into four subgroups (PIGM, RED, CONTROL, PIGM + RED), and trends among them were analyzed. Results: We found a strong correlation between VISIA® red area scores and D-OCT vascular density at 300 µm depth, confirming VISIA®’s effectiveness for assessing facial vascularity. Wrinkle count was highest in areas with UV spots, particularly in the PIGM and PIGM + RED groups. Conversely, low attenuation coefficients and dermal density were observed in regions with low UV spots but high red areas. Intermediate subgroups (CONTROL and PIGM + RED) displayed varying parameters. Conclusions: Non-invasive imaging devices are effective in evaluating facial aging and distinguishing between aging subtypes. This study identified two intermediate aging types in addition to the hypertrophic and atrophic subtypes.